2011
DOI: 10.1177/0306624x11428315
|View full text |Cite
|
Sign up to set email alerts
|

Review of Risk Assessment Instruments for Juvenile Sex Offenders

Abstract: Risk assessment is considered to be a key element in the prevention of recidivism among juvenile sex offenders (JSOs), often by imposing long-term consequences based on that assessment. The authors reviewed the literature on the predictive accuracy of six well-known risk assessment instruments used to appraise risk among JSOs: the Juvenile Sex Offender Assessment Protocol-II (J-SOAP-II), Juvenile Sexual Offence Recidivism Risk Assessment Tool-II (J-SORRAT-II), Estimate of Risk of Adolescent Sexual Offence Reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 56 publications
(124 reference statements)
0
50
0
4
Order By: Relevance
“…The literature spanning the past three decades has predominately focused on identifying both risk factors for future reoffense (Hempel, Buck, Cima, & van Marle, 2013;Miner, 2002) as well as investigating how various social and ecological frameworks explain the onset of sexually problematic behaviors (Ryan, 2010a;Seto & Lalumière, 2010). It is without question that these important advancements have vastly contributed to the field's knowledge, but at the cost of neglecting to identify resilience characteristics, protective factors, or evaluate the efficacy behind several conventional therapeutic modalities (Efta-Breitbach & Freeman, 2004;Spice et al, 2013;Yoder, 2014).…”
Section: Donna Ruchmentioning
confidence: 99%
“…The literature spanning the past three decades has predominately focused on identifying both risk factors for future reoffense (Hempel, Buck, Cima, & van Marle, 2013;Miner, 2002) as well as investigating how various social and ecological frameworks explain the onset of sexually problematic behaviors (Ryan, 2010a;Seto & Lalumière, 2010). It is without question that these important advancements have vastly contributed to the field's knowledge, but at the cost of neglecting to identify resilience characteristics, protective factors, or evaluate the efficacy behind several conventional therapeutic modalities (Efta-Breitbach & Freeman, 2004;Spice et al, 2013;Yoder, 2014).…”
Section: Donna Ruchmentioning
confidence: 99%
“…Conducting risk‐assessments is well intentioned, but practitioners should proceed with caution as the literature is quite mixed on juvenile sexual offender risk assessments and their predictive utility. That said, some evidence suggests the predictive utility of assessments such as the J‐SOAP‐II and the J‐SORRAT‐II were stronger compared to others (Hempel, Buck, Cima, & van Merle, ), which is likely a result of these assessments being specifically designed for youth assessing sexual recidivism. Due to the low re‐offense rates of juvenile sexual offenders, it is possible that risk assessments lead to overestimation of “high risk” youth.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an effort to utilize risk assessments to identify treatment and supervision needs. Assessment instruments such as the Juvenile Sex Offender Assessment Protocol‐II (J‐SOAP‐II), Juvenile Sexual Offence Recidivism Risk Assessment Tool‐II (J‐SORRAT‐II), and the Structured Assessment of Violent Risk in Youth (SAVRY) are frequently used in assessing risk among juvenile sexual offenders (Hempel, Buck, Cima, & van Merle, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations were weaker, but sill significant, between psychopathy and nonviolent recidivism (r= .16), however no significant relationship was detected between sexual recidivism and psychopathy. Similarly, a recent review of the PCL:YV found that the measure predicted nonsexual violent and general recidivism with moderate accuracy, but was not a strong predictor of future sexual offending (Hempel, Buck, Cima, & van Marle, 2013).…”
Section: Psychopathymentioning
confidence: 96%